Pengaruh penambahan sekam padi terhadap kuat tekan dan penyerapan air bata ringan jenis cellular lightweight concrete (clc) - Sulistyo Widiatmoko; Heru Sukanto; Purwadi Joko Widodo (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
Lightweight concrete foam technology obtained by adding foaming agent (liquid form) into the concrete mix. Lightweight concrete has more advatages than conventional bricks. Lightweight concrete can reduce more structural weight on building. This research use rice husk as an added ingredient on lightweight concrete. The main objective of this study is to investigate the effect of rice husk addition on compressive strength and water absorption of cellular lightweight concrete. Variation of rice husk adding on lightweight concrete is 0% ; 0,25%; 0,5%; 0,75%; and 1%. Compressive Strength and Water Absorption test were performed using SNI 3421-2011 and SNI 03-0349-1989 standard respectively. Density test was performed to ensure that sample specimens appertain lightweight concrete. The observations during the experiment and test show that the lightweight concrete with 0,5% addition of rice husk has the highest value of compressive strength which 5.30 Mpa. The value of water absorption is directly proportional to the addition of rice husk, where the highest value shown on 1% addition of rice husk. Increasing value of water absorption occurs because rice husk can keep water and can’t easy to remove water content when be dried.